Composite positive pole piece and lithium ion battery applying same

By designing a composite positive electrode sheet in a lithium-ion battery, regulating the structural parameters of the active layer, optimizing the diffusion path of lithium ions, the problem of low lithium ion transmission efficiency is solved and the battery performance is improved.

CN119480888AInactive Publication Date: 2025-02-18HUIZHOU EVE POWER CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411588887.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The low lithium ion transmission efficiency in lithium-ion batteries limits the battery's high power, fast charging and long-life performance.

Method used

By designing a composite positive electrode sheet, the thickness, diffusion coefficient and porosity of the first active layer and the second active layer are regulated, the diffusion path of lithium ions is optimized, and the benign coordination between different active layers is achieved, and the charge transfer impedance is reduced.

Benefits of technology

It improves the lithium-ion transmission efficiency of lithium-ion batteries and enhances the battery's power, cycle and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480888A_ABST
    Figure CN119480888A_ABST
Patent Text Reader

Abstract

The invention provides a composite positive pole piece and a lithium ion battery applying the composite positive pole piece, the composite positive pole piece comprises a current collector, at least one surface of the current collector is respectively provided with a first active layer and a second active layer which are compounded with each other, the first active layer is close to the current collector, and the second active layer is far away from the current collector; the diffusion resistance of the first active layer is # imgabs 0 #, and the diffusion resistance of the second active layer is # imgabs 1 #. In the composite positive pole piece, the following relational expression is satisfied: D1 < lt >; l1 is the thickness of the first active layer, L2 is the thickness of the second active layer, and D2 is the thickness of the second active layer; d1 and D2 are diffusion coefficients of the first active layer and the second active layer respectively; epsilon1 and Epsilon2 are the porosity of the first active layer and the porosity of the second active layer respectively. By optimizing the gradient porosity of the positive pole piece in the use process, the composite positive pole piece with low lithium ion diffusion resistance is obtained, so that the purpose of improving the lithium ion transmission efficiency of the lithium ion battery is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of lithium-ion batteries, and particularly relates to a composite positive electrode sheet and a lithium-ion battery using the same. Background Art

[0002] Lithium-ion batteries have great advantages in improving energy efficiency and promoting the development of new energy. At the same time, they can also reduce manufacturing costs, bringing people a more efficient, environmentally friendly and economical way of energy utilization. And lithium-ion batteries are one of the most widely used rechargeable battery types at present.

[0003] The performance requirements of lithium-ion batteries that have attracted much attention, such as high power, fast charging, long life, etc., are largely restricted by the lithium-ion transmission efficiency. This is because the transmission of lithium ions in the battery involves multiple steps, including diffusion inside the electrode material, transfer at the electrode / electrolyte interface, and migration through the electrolyte. And the rates of these transmission processes will directly affect the performance of the battery.

[0004] Therefore, in order to further expand the application scope of lithium-ion batteries, it is necessary to improve the lithium-ion transmission effect in lithium-ion batteries. At present, researchers have explored various strategies to enhance the lithium-ion transmission efficiency of lithium-ion batteries, such as improving the conductivity of the positive and negative electrode materials, using electrolytes with high conductivity, etc. However, the research and development and application of new materials will have problems such as long R & D cycles, large investments, and high risks. Summary of the Invention

[0005] In order to improve the lithium-ion transmission efficiency of lithium-ion batteries, this application provides a composite positive electrode sheet and a lithium-ion battery using the same.

[0006] According to one aspect of this application, a composite positive electrode sheet is provided. The composite positive electrode sheet includes a current collector, and a first active layer and a second active layer that are composited with each other are respectively disposed on at least one surface of the current collector. The first active layer is close to the current collector, and the second active layer is far from the current collector; the diffusion resistance of the first active layer is The diffusion resistance of the second active layer is In the composite positive electrode sheet, the following relational expression is satisfied: D1 < D2, and, wherein, L1 and L2 are the thicknesses of the first active layer and the second active layer respectively; D1 and D2 are the diffusion coefficients of the first active layer and the second active layer respectively; ε1 and ε2 are the porosities of the first active layer and the second active layer respectively.

[0007] The present application can improve the lithium ion transmission efficiency of lithium-ion batteries by optimizing the structural design of the positive electrode sheet. Specifically, the present application controls the diffusion resistance of the first active layer and the second active layer respectively by regulating the thickness, diffusion coefficient and porosity of the first active layer and the second active layer to achieve different lithium ion diffusion rates. The present application cleverly controls the spatial pore distribution from the current collector to the multilayer active material and then to the electrolyte, and utilizes the above-mentioned lithium ion diffusion rate difference to achieve benign synergy between different active layers, thereby improving the charge transfer impedance of the composite positive electrode sheet. By further regulating the diffusion resistance ratio between the first active layer and the second active layer, the power, cycle and safety performance of the lithium-ion battery can be further enhanced. Therefore, the present application obtains a composite positive electrode sheet with low lithium ion diffusion resistance by optimizing the gradient porosity of the positive electrode sheet during use, thereby achieving the purpose of improving the lithium ion transmission efficiency of the lithium-ion battery.

[0008] Preferably, 1.0×10 -15 ≤D1≤1.0×10 -10 .

[0009] Preferably, 1.0×10 -12 ≤D2≤1.0×10 -10 .

[0010] Preferably, the thickness L1 of the first active layer is ≤800 μm; and / or the thickness L2 of the second active layer is ≤600 μm.

[0011] Preferably, 60 μm ≤ L1 ≤ 200 μm.

[0012] Preferably, 10 μm ≤ L2 ≤ 80 μm.

[0013] Preferably, the porosity ε1 of the first active layer and the porosity ε2 of the second active layer satisfy the following relationship: 2%≤ε2-ε1≤30%. The inventor unexpectedly discovered that when the porosity in the second active layer is lower than that in the first active layer, it is easy to affect the wetting of the electrolyte electrode, thereby increasing the internal resistance of the lithium-ion battery; when the porosity of the second active layer is much higher than that of the first active layer, it is easy to increase the transmission path of lithium ions in the electrode, thereby affecting the migration resistance of lithium ions. Therefore, the present application can improve the DCR cycle growth and power performance of the battery cell by further regulating the porosity of the second active layer to be higher than that of the first active layer and limiting it to the above range.

[0014] Preferably, 5%≤ε2-ε1≤10%. By further limiting the porosity difference between the first active layer and the second active layer, the power performance and cycle stability can be further enhanced.

[0015] Preferably, the oxide-based active material includes at least one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, and lithium manganese oxide.

[0016] Preferably, the first active layer further includes a first conductive agent, and the second active layer further includes a second conductive agent, the mass content of the first conductive agent is less than the mass content of the second conductive agent, and the mass content of the first conductive agent is not higher than 1.5%.

[0017] Preferably, in the second active layer, the mass content of the second conductive agent is 0.5-2%.

[0018] Preferably, in the first active layer, the mass content of the first positive electrode active material is 90-99%; and / or, in the second active layer, the mass content of the second positive electrode active material is 90-98.5%.

[0019] Preferably, the conductive agent includes at least one of conductive carbon black SP and carbon nanotubes CNT.

[0020] Preferably, the first active layer comprises a first positive electrode active material, and the first positive electrode active material comprises lithium manganese iron phosphate LiMn 1-x Fe x PO4, wherein 0.2≤x≤1; and / or, the second active layer comprises a second positive electrode active material, and the second positive electrode active material comprises an oxide-based active material.

[0021] Preferably, the median particle size D of lithium manganese iron phosphate is 50(M1) The median particle size D of oxide active materials 50(M2) Satisfies the following relationship: D 50(M1) -D 50(M2) >3μm; among which, the particle size D of lithium manganese iron phosphate 50(M1) Satisfy 1μm≤D 50(M1) ≤5μm; and / or, the particle size D of the oxide active material 50(M2) Satisfy 2μm≤D 50(M2) ≤10μm.

[0022] The second aspect of the present application provides a lithium ion battery, which includes the composite positive electrode sheet. The present application can obtain a lithium ion battery with good cycle performance and power performance by applying the composite positive electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A cross-sectional view of the composite positive electrode sheet provided in Example 1 of the present application;

[0024] In the above drawings, the meanings of the reference numerals are as follows: 1. current collector; 2. first active layer; 3. second active layer. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in this application will be clearly and completely described below in conjunction with the embodiments of this application and the drawings in the embodiments. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.

[0026] Example 1

[0027] 1. Raw materials required for composite positive electrode sheets

[0028] Weigh the required raw materials according to the materials shown in Table 1.

[0029] Table 1. Raw materials for preparing composite positive electrode sheets

[0030]

[0031] 2. Method for preparing composite positive electrode sheet and lithium ion battery

[0032] According to the formulas provided in Table 1, the first positive electrode active material, the conductive agent, and the binder are configured into a first slurry, and the second positive electrode active material, the conductive agent, and the binder are configured into a second slurry. Subsequently, the first slurry is coated on the surface of the current collector 1 by coating, and the first active layer 2 is obtained after drying; the second slurry is coated on the surface of the first active layer 2 and dried to obtain the second active layer 3. Repeat the above operation so that the first active layer 2 and the second active layer 3 are covered on both surfaces of the current collector 1. The cross-sectional view of the composite positive electrode sheet provided in this embodiment is shown in FIG. Figure 1 As shown. The thickness of the first active layer 2 is 68 μm, and the thickness of the second active layer 3 is 19 μm. The ratio of the diffusion resistance of the first active layer 2 to the diffusion resistance of the second active layer 3 prepared in this embodiment is 6.89×10 -4 .

[0033] The composite positive electrode sheet, graphite negative electrode sheet, separator and electrolyte are made into a lithium-ion battery.

[0034] Example 2

[0035] This embodiment prepares a composite positive electrode sheet and a lithium-ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite positive electrode sheet in this embodiment, the ratio of the diffusion resistance of the first active layer 2 to the diffusion resistance of the second active layer 3 is 2.5×10 -8 Except for the above differences, the operation steps for preparing the composite positive electrode sheet and lithium-ion battery in this embodiment are strictly consistent with those in Example 1.

[0036] Example 3

[0037] This embodiment prepares a composite positive electrode sheet and a lithium-ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite positive electrode sheet in this embodiment, the ratio of the diffusion resistance of the first active layer 2 to the diffusion resistance of the second active layer 3 is 2.5×10 -1 Except for the above differences, the operation steps for preparing the composite positive electrode sheet and lithium-ion battery in this embodiment are strictly consistent with those in Example 1.

[0038] Example 4

[0039] This embodiment prepares a composite positive electrode sheet and a lithium-ion battery with reference to the formula and method provided in Embodiment 1. The difference from Embodiment 1 is that when preparing the composite positive electrode sheet in this embodiment, the difference between the porosity of the first active layer 2 and the porosity of the second active layer 3 is 26%. Except for the above difference, the operating steps for preparing the composite positive electrode sheet and the lithium-ion battery in this embodiment are strictly consistent with those in Embodiment 1.

[0040] Example 5

[0041] This embodiment prepares a composite positive electrode sheet and a lithium-ion battery with reference to the formula and method provided in Embodiment 1. The difference from Embodiment 1 is that when preparing the composite positive electrode sheet in this embodiment, the difference between the porosity of the first active layer 2 and the porosity of the second active layer 3 is 10%. Except for the above difference, the operating steps for preparing the composite positive electrode sheet and the lithium-ion battery in this embodiment are strictly consistent with those in Embodiment 1.

[0042] Example 6

[0043] This embodiment prepares a composite positive electrode sheet and a lithium-ion battery with reference to the formula and method provided in Embodiment 1. The difference from Embodiment 1 is that when preparing the composite positive electrode sheet in this embodiment, the difference between the porosity of the first active layer 2 and the porosity of the second active layer 3 is 3.1%. Except for the above difference, the operating steps for preparing the composite positive electrode sheet and the lithium-ion battery in this embodiment are strictly consistent with those in Embodiment 1.

[0044] Example 7

[0045] This embodiment prepares a composite positive electrode sheet and a lithium-ion battery with reference to the formula and method provided in Embodiment 1. The difference from Embodiment 1 is that when preparing the composite positive electrode sheet in this embodiment, the thickness of the first active layer 2 is L1=98 μm, and the thickness of the second active layer 3 is L2=24 μm. Except for the above differences, the operation steps for preparing the composite positive electrode sheet and the lithium-ion battery in this embodiment are strictly consistent with those in Embodiment 1.

[0046] Example 8

[0047] This embodiment prepares a composite positive electrode sheet and a lithium-ion battery with reference to the formula and method provided in Embodiment 1. The difference from Embodiment 1 is that when preparing the composite positive electrode sheet in this embodiment, the thickness of the first active layer 2 is L1=132 μm, and the thickness of the second active layer 3 is L2=52 μm. Except for the above differences, the operation steps for preparing the composite positive electrode sheet and the lithium-ion battery in this embodiment are strictly consistent with those in Embodiment 1.

[0048] Example 9

[0049] This embodiment prepares a composite positive electrode sheet and a lithium-ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite positive electrode sheet in this embodiment, the thickness of the first active layer 2 is L1=218, and the thickness of the second active layer 3 is L2=74. Except for the above differences, the operating steps for preparing the composite positive electrode sheet and the lithium-ion battery in this embodiment are strictly consistent with those in Example 1.

[0050] Example 10

[0051] This embodiment prepares a composite positive electrode sheet and a lithium-ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite positive electrode sheet in this embodiment, the second positive electrode active material used in the second active layer 3 is lithium cobalt oxide. Except for the above difference, the operating steps for preparing the composite positive electrode sheet and the lithium-ion battery in this embodiment are strictly consistent with those in Example 1.

[0052] Embodiment 11

[0053] This embodiment prepares a composite positive electrode sheet and a lithium-ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite positive electrode sheet in this embodiment, the second positive electrode active material used in the second active layer 3 is lithium manganese oxide. Except for the above difference, the operating steps for preparing the composite positive electrode sheet and the lithium-ion battery in this embodiment are strictly consistent with those in Example 1.

[0054] Comparative Example 1

[0055] This comparative example prepares a composite positive electrode sheet and a lithium-ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite positive electrode sheet, the first positive electrode active material and the second positive electrode active material are mixed and then coated on the surface of the current collector 1. In addition to the above differences, the operating steps for preparing the composite positive electrode sheet and the lithium-ion battery in this comparative example are strictly consistent with those in Example 1.

[0056] Specifically, the steps for preparing the composite positive electrode sheet are as follows: according to the formula provided in Table 1, the first positive electrode active material, the second positive electrode active material, the conductive agent, and the binder are configured into a composite slurry. Then, the composite slurry is coated on the surface of the current collector 1 by coating, and a composite active layer is obtained after drying. The above operation is repeated so that the two surfaces of the current collector 1 are covered with the composite active layer.

[0057] Comparative Example 2

[0058] This comparative example prepares a composite positive electrode sheet and a lithium-ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite positive electrode sheet, the second slurry is first coated on the surface of the current collector 1, and then the first slurry is coated. In addition to the above differences, the operation steps for preparing the composite positive electrode sheet and the lithium-ion battery in this comparative example are strictly consistent with those in Example 1.

[0059] Specifically, the steps of preparing the composite positive electrode sheet are as follows: according to the formula provided in Table 1, the first positive electrode active material, the conductive agent, and the binder are configured into a first slurry, and the second positive electrode active material, the conductive agent, and the binder are configured into a second slurry. Then, the second slurry is coated on the surface of the current collector 1 by coating, and the second active layer 3 is obtained after drying; the first slurry is coated on the surface of the second active layer 3 and dried to obtain the first active layer 2. Repeat the above operation so that the first active layer 2 and the second active layer 3 are covered on both surfaces of the current collector 1.

[0060] Test Case

[0061] 1. Test subjects

[0062] Composite positive electrode sheets and lithium-ion batteries prepared in Examples 1 to 11 and Comparative Examples 1 to 2.

[0063] 2. Test Method

[0064] (1) Cycle performance: ① The prepared battery was charged at a constant current of 1 / 3C and a constant voltage of 0.05C, with a voltage range of 2.5-4.25V, and the charge and discharge cycle was repeated 3 times, and the capacity was calibrated at the last time; ② It was left for 10 minutes; ③ It was charged at a constant current of 0.5C0 to 4.25V, charged at a constant voltage of 0.05C0, left for 10 minutes, and then discharged at 1C0 to 2.5V, left for 10 minutes; ④ Step 3 was repeated until the SOH reached 80%.

[0065] (2) DCR: ① The prepared battery was charged at a constant current of 1 / 3C and a constant voltage of 0.05C, with a voltage range of 2.5-4.25V, and the charge and discharge cycle was repeated 3 times, and the capacity was calibrated at the last time; ② It was left for 10 minutes; ③ It was charged at a constant current of 1 / 3C0 to 4.25V, and the constant voltage was charged to a cut-off current of 0.05C0, and left for 10 minutes; It was discharged at a constant current of 1 / 3C0 to 50% SOC, and left for 60 minutes; ④ It was discharged at a constant current of 1C0 for 30 seconds, and left for 10 minutes; ⑤ It was discharged at a constant current of 1 / 3C0 until 2.5V.

[0066] (3) Power performance: ① The prepared battery was charged at a constant current of 1 / 3C and a constant voltage of 0.05C, with a voltage range of 2.5-4.25V, and the charge and discharge cycle was repeated 3 times, and the capacity was calibrated at the last time; ② It was left for 30 minutes; ③ It was charged at a constant current of 0.2C0 to 4.25V, and the constant voltage was charged to a cut-off current of 0.02C0, and left for 30 minutes; ④ It was discharged at 1 / 3C0 to 90% SOC and left for 180 minutes; ⑤ It was discharged at 1800W for 10 seconds and left for 5 minutes; ⑥ It was discharged at 1 / 3C0 to 30% SOC and left for 60 minutes; ⑦ It was discharged at 1500W for 10 seconds and left for 5 minutes;

[0067] (4) GITT test: ① The prepared battery was charged at a constant current of 1 / 3C and a constant voltage of 0.05C, with a voltage range of 2.5-4.25V, and the charge and discharge cycle was repeated three times, and the capacity was calibrated at the last time; ② Let it stand for 30 minutes; ③ Charge at a constant current of 0.1C0 to 4.25V, charge at a constant voltage to a cutoff current of 0.05C0, and let it stand for 60 minutes; ④ Discharge at 0.1C0 for 10 minutes and let it stand for 60 minutes; ⑤ Repeat step ④ until the voltage drops to 2.5V.

[0068] 3. Test results and analysis

[0069] In the prior art, lithium manganese iron phosphate (LMFP) has become the focus of lithium-ion battery development while taking into account high energy density, safety and low cost. Its development is limited by its low ionic conductivity, dual platform effect, etc. When studying to improve the positive active material of LMFP, the inventor found that the internal resistance of the cycle increased rapidly after the lithium manganese iron phosphate was mixed with the oxide active material, which was specifically manifested as an abnormal increase in the medium and low frequency impedance. Through exploration, the inventor found that the reason for the abnormal growth was that when lithium manganese iron phosphate and oxide active materials were used to prepare mixed electrodes, there were obvious differences in the particle size and particle size distribution of the two, resulting in a more complex pore distribution of the mixed electrode. The porosity and pore tortuosity limit the transmission of lithium ions, which in turn leads to poor cycle performance and power performance. As shown in the electrode structure prepared in Comparative Example 1, its DCR growth rate is as high as 110.98%.

[0070] The experimental data of Examples 1 to 11 show that the present invention optimizes the structural design of the positive electrode sheet and adjusts the diffusion resistance ratio between the first active layer and the second active layer to meet

[0071] In addition, it can be seen from Comparative Example 2 that the structural settings of the first active layer and the second active layer have a sequential relationship. When the two are interchanged, it will not only affect the diffusion resistance, but also the DCR growth rate, cycle and power performance of the battery cell.

[0072] It can be seen from Examples 1 to 11 that the present invention can also adjust the porosity difference between the first active material and the second positive electrode active material, the D 50 , and then utilize the volume shrinkage and expansion differences of different active materials during the lithium ion insertion and extraction cycle to further optimize the gradient porosity of the positive electrode sheet, thereby significantly improving the transmission of lithium ions and enhancing the cycle performance and power performance of lithium-ion batteries.

[0073] The data of Example 10 and Example 11 confirm that when the first positive electrode active material is lithium manganese iron phosphate, the second positive electrode active material oxide active material can be lithium nickel cobalt manganese oxide, lithium cobalt oxide, and lithium manganese oxide, which not only has a lower DCR growth rate, but also maintains good cycle performance and power performance.

[0074] Table 2. Related parameters of each embodiment and comparative example in this test example

[0075] Group <![CDATA[R2 / R1]]> <![CDATA[ε2-ε1]]> <![CDATA[D 50(M2) ]]> <![CDATA[D 50(M2) ]]> <![CDATA[L1 / μm]]> <![CDATA[L2 / μm]]> Example 1 <![CDATA[6.89×10 -4 ]]> 17.4% 1.52 4.41 67.4 18.6 Example 2 <![CDATA[2.5×10 -8 ]]> 16.9% 1.36 4.63 22.6 74.2 Example 3 <![CDATA[2.5×10 -1 ]]> 3.2% 1.22 5.09 81.9 26.3 Example 4 <![CDATA[3.2×10 -7 ]]> 26% 1.52 5.09 67.4 18.6 Example 5 <![CDATA[9.9×10 -4 ]]> 10% 1.22 4.41 67.4 18.6 Example 6 <![CDATA[8.6×10 -2 ]]> 3.1% 1.36 4.63 67.4 18.6 Example 7 <![CDATA[6.3×10 -3 ]]> 14.3% 1.36 4.41 98 24 Example 8 <![CDATA[2.2×10 -4 ]]> 19.8% 1.52 4.63 132 52 Example 9 <![CDATA[9.6×10 -5 ]]> 12.6% 1.22 5.09 218 74 Example 10 <![CDATA[9.7×10 -2 ]]> 28.5% 1.22 7.4 67.4 18.6 Embodiment 11 <![CDATA[1.2×10 -3 ]]> 32.3% 1.22 15.3 67.4 18.6 Comparative Example 1 / / / / / / Comparative Example 2 <![CDATA[1.5×10 3 ]]> -17.4% 4.41 1.52 18.6 67.4

[0076] Table 3. Test results of this test case

[0077] Group Cycle performance Power performance DCR Growth Rate Example 1 1489cls 2.88V 45.89% Example 2 1598cls 2.93V 43.25% Example 3 1466cls 2.69V 56.39% Example 4 1523cls 2.92V 44.92% Example 5 1499cls 2.87V 45.96% Example 6 1402cls 2.70V 52.93% Example 7 1452cls 2.79V 51.38% Example 8 1479cls 2.90V 46.01% Example 9 1511cls 2.97V 44.79% Example 10 1378cls 2.58V 62.58% Embodiment 11 1326cls 2.62V 67.44% Comparative Example 1 1092cls 2.43V 110.98% Comparative Example 2 890cls 2.39V 98.72%

[0078] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person skilled in the art should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A composite positive electrode sheet, characterized in that: The composite positive electrode sheet includes a current collector, and a first active layer and a second active layer which are composited with each other are respectively disposed on at least one surface of the current collector. The first active layer is close to the current collector, and the second active layer is far from the current collector; The diffusion resistance of the first active layer is The diffusion resistance of the second active layer is In the composite positive electrode sheet, the following relational expression is satisfied: D1 < D2, and, wherein, L1 and L2 are the thicknesses of the first active layer and the second active layer respectively; D1 and D2 are the diffusion coefficients of the first active layer and the second active layer respectively; ε1 and ε2 are the porosities of the first active layer and the second active layer respectively.

2. The composite positive electrode sheet according to claim 1, characterized in that: The thickness L1 of the first active layer ≤ 800 μm; and / or, the thickness L2 of the second active layer ≤ 600 μm.

3. The composite positive electrode sheet according to claim 1, characterized in that: The porosity ε1 of the first active layer and the porosity ε2 of the second active layer satisfy the following relational expression: 2% ≤ ε2 - ε1 ≤ 30%.

4. The composite positive electrode sheet according to claim 1, characterized in that: A first conductive agent is further included in the first active layer, and a second conductive agent is further included in the second active layer. The mass content of the first conductive agent is less than the mass content of the second conductive agent, and the mass content of the first conductive agent is not higher than 1.5%.

5. The composite positive electrode sheet according to claim 4, characterized in that: In the second active layer, the mass content of the second conductive agent is 0.5 - 2%.

6. The composite positive electrode sheet according to claim 4, characterized in that: In the first active layer, the mass content of the first positive electrode active material is 90 - 99%; and / or, in the second active layer, the mass content of the second positive electrode active material is 90 - 98.5%.

7. The composite positive electrode sheet according to any one of claims 1 to 6, characterized in that: The first active layer includes a first positive electrode active material, and the first positive electrode active material includes lithium iron manganese phosphate LiMn 1-x Fe x PO4, wherein 0.2≤x≤1; and / or, the second active layer comprises a second positive electrode active material, and the second positive electrode active material comprises an oxide-based active material.

8. The composite positive electrode sheet according to claim 7, characterized in that: The median particle size D of the lithium manganese iron phosphate 50(M1) The median particle size D of the oxide active material 50(M2) The following relationship is satisfied: D 50(M2) -D 50(M1) >3μm; Wherein, the median particle size D of the lithium manganese iron phosphate is 50(M1) Satisfy 1μm≤D 50(M1) ≤5μm; And / or, the median particle size D of the oxide active material 50(M2) Satisfy 2μm≤D 50(M2) ≤10μm.

9. The composite positive electrode sheet according to claim 7, characterized in that: The oxide-based active material includes at least one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, and lithium manganese oxide.

10. A lithium ion battery, characterized in that: The lithium ion battery includes the composite positive electrode sheet according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Layered electrode with high rate top layer

    CN113544874A

  • Composite electrode and preparation method thereof, battery and electric equipment

    CN115810719A

  • Lithium manganese iron phosphate positive electrode material and preparation method thereof, positive electrode plate and preparation method thereof, lithium ion battery and electric equipment

    CN117577832A

  • Positive pole piece, preparation method thereof and lithium ion battery

    CN117894916A

  • Fast charging type secondary battery and preparation method thereof

    CN118156624A